2019
DOI: 10.3233/jad-190288
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Anti-Dementia Medication on the Risk of Death and Causes of Death in Alzheimer’s Disease

Abstract: Background: The Finnish population offers many advantages for evaluating the impact of anti-dementia medication on mortality in Alzheimer's disease (AD) due to broad range of individual-level data collected in national health and social care registries and the fact that Finland has one of the highest mortality rates for dementia globally. Objective: The aim of this study was to investigate the association of anti-dementia medication with 2-year risk of death and all-cause mortality in patients with AD. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…The main reason was the participants considered that AD is currently incurable and the diagnosis would be of little signi cance, indicating that some people are still insu ciently aware of AD treatment. Although AD cannot be completely cured at present, a large number of studies have shown that early diagnosis and reasonable treatment can effectively delay disease progression and reduce the economic burden on families and society [18][19][20]. In 2019, the China Food and Drug Administration (CFDA) approved Sodium Oligomannate for the treatment of mild-moderate AD, which can effectively improve the cognitive function of AD patients and delay the progression of the disease [21][22][23].…”
Section: Discussionmentioning
confidence: 99%
“…The main reason was the participants considered that AD is currently incurable and the diagnosis would be of little signi cance, indicating that some people are still insu ciently aware of AD treatment. Although AD cannot be completely cured at present, a large number of studies have shown that early diagnosis and reasonable treatment can effectively delay disease progression and reduce the economic burden on families and society [18][19][20]. In 2019, the China Food and Drug Administration (CFDA) approved Sodium Oligomannate for the treatment of mild-moderate AD, which can effectively improve the cognitive function of AD patients and delay the progression of the disease [21][22][23].…”
Section: Discussionmentioning
confidence: 99%
“…It has also been shown that ChEIs and memantine are not effective in restoring cognitive function and relieving neuropsychiatric symptoms in patients with poor overall outcomes 36 . However, ChEIs and memantine reduce the risk of death in patients with AD, and donepezil has a greater ability to reduce the risk of death than memantine 34 . High doses of Rivastigmine patches have been shown to be very effective in functional recovery and initial diagnosis.…”
Section: Memantine Therapy For Admentioning
confidence: 99%
“…The loss of cholinergic nerves in the basal forebrain of AD patients results in the denervation of presynaptic cholinergic neurons. ChEIs compensate for the decrease in cholinergic energy in patients by inhibiting acetylcholine catabolism and enhancing interneural message transmission 34 . Memantine inhibits the excessive activation of NMDA receptors, thereby antagonizing glutamine‐mediated excitotoxicity to neuronal damage.…”
Section: Memantine Therapy For Admentioning
confidence: 99%
See 1 more Smart Citation
“…This modelling approach will give us an estimation of the effect of various individual characteristics on care transition. In particular, we can estimate the effect of separate pharmacological therapies on care transition by including one dummy variable 𝛽𝛽 𝑚𝑚𝑑𝑑𝑑𝑑 𝑡𝑡−1 per therapy to the equation (Linna, Vuoti, et al, 2019). Continuing, we can also model the effect of pharmaceutical therapies on risk of dying by considering death as one (absorbing) long-term state (Halminen, Vesikansa, et al, 2021).…”
Section: Risk Of a Care Transitionmentioning
confidence: 99%